PENDUGAAN DAMPAK KEBIJAKAN SUKU BUNGA TERHADAP KINERJA EKONOMI MAKRO SEKTOR PERIKANAN: ANALISIS JALUR INVESTASI DAN EKSPOR MENGGUNAKAN PENDEKATAN MODEL STRUCTURAL VECTOR AUTOREGRESSION - Tajerin Tajerin (Universitas Gadjah Mada, 2005)
Rapid and complicated development of system, operation, and money market instrument contribute in separation process between monetary and real sectors activities that deminise the effectiveness of monetary policy. Transmission mechanism test by using investment and net export channels indicated that increase in the interest rate of Indonesian Bank Certificate had negative impact on the performance, investment, export and Product Domestic Brutto of fisheries sectors. Monetary instrument should be designed to drive aggregate demand in fisheries sectors in accordance with economical capacity from supply side. On the other hand, proactive effort in fisheries sectors was needed through the monetary policy from Bank of Indonesia to increase productivity of macro economy in fisheries sectors. Rapid and complicated development of system, operation, and money market instrument contribute in separation process between monetary and real sectors activities that deminise the effectiveness of monetary policy. Transmission mechanism test by using investment and net export channels indicated that increase in the interest rate of Indonesian Bank Certificate had negative impact on the performance, investment, export and Product Domestic Brutto of fisheries sectors. Monetary instrument should be designed to drive aggregate demand in fisheries sectors in accordance with economical capacity from supply side. On the other hand, proactive effort in fisheries sectors was needed through the monetary policy from Bank of Indonesia to increase productivity of macro economy in fisheries sectors.